Intellectual Property Protection of Multinational Enterprises’ Algorithm in Cross-Border Data Flows - Ling, Yan (Transactions on Social Science, Education and Humanities Research, 2024)
Among the fierce AI competition of MNE, algorithm represent the core capability in the market. However, the increasing demands for transparency, driven by national security and privacy concerns, have significantly undermined the protection of these algorithms. The traditional method of safeguarding algorithms through trade secrets has become increasingly ineffective, contributing to the potential decline of numerous AI-focused multinational enterprises. In response to this dilemma, this paper argues for the innovation of algorithms to be recognized and established as a new category of intellectual property right. Key recommendations also include the enhancement of international cooperation and the development of a comprehensive government guidance framework. This framework emphasizes clear evaluative criteria, expert certification, efficient evaluation processes, protection of sensitive information, transparency, accountability, and international collaboration. By implementing these strategies, governments and regulatory bodies can foster an environment that protects MNEs’ innovative capabilities while accommodating the public and regulatory demands for transparency and accountability in AI applications.